Monsters, Chimeras, Masks or Gods? - Paweł Gołyźniak (Ksiegarnia Akademicka Publishing, 2013)
The National Museum in Krakow contains an outstanding set of gems collected by Constantine Schmidt-Ciążyński (1818-1889). Within this extensive group of objects, two very rare intaglios bearing a particular intriguing motif, the double-headed device, stand out from the rest. Since the very beginning, scholars have interpreted this kind of depiction differently and many different hypotheses have been drawn. This paper aims to explain the meaning of this strange iconography and from whence it originated.